1998
DOI: 10.1107/s0907444998004119
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Prior Phase Information Strengthens Maximum-Likelihood Structure Refinement

Abstract: The application of a maximum-likelihood analysis to the problem of structure re®nement has led to striking improvements over the traditional least-squares methods. Since the method of maximum likelihood allows for a rational incorporation of other sources of information, we have derived a likelihood function that incorporates experimentally determined phase information. In a number of different test cases, this target function performs better than either a least-squares target or a maximum-likelihood function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
188
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(188 citation statements)
references
References 25 publications
(24 reference statements)
0
188
0
Order By: Relevance
“…Further rounds of refinement were also carried out with Refmac5. 28,31 Between refinement rounds, coordinates and electron density maps were studied and adjusted where needed with Xfit. 32 Noncrystallographic symmetry (NCS) restraints were applied to the molecules of the asymmetric unit during refinement and removed for the final round.…”
Section: Data Collection and Refinementmentioning
confidence: 99%
See 1 more Smart Citation
“…Further rounds of refinement were also carried out with Refmac5. 28,31 Between refinement rounds, coordinates and electron density maps were studied and adjusted where needed with Xfit. 32 Noncrystallographic symmetry (NCS) restraints were applied to the molecules of the asymmetric unit during refinement and removed for the final round.…”
Section: Data Collection and Refinementmentioning
confidence: 99%
“…27 In order to locate the PYR ligand, a difference Fourier map was calculated with the Collaborative Computational Project 4 (CCP4) 28 suite of programs (S Fall , 29 Sigma-A, 30 and Refmac5 31 for rigid body refinement) using the PDB coordinates (1NOU) of the native β-hexosaminidase B. 1 PYR, sugars, SO 4 ions, and water molecules were not included in the initial rigid body refinement and map calculations but were added in subsequent rounds.…”
Section: Data Collection and Refinementmentioning
confidence: 99%
“…Re®nements were repeated with three different re®nement targets: least-squares residual (LSQ), maximum likelihood based on amplitudes (MLF; Pannu & Read, 1996) and maximum likelihood incorporating experimental phase informa- tion (MLHL; Pannu et al, 1998). In all cases a¯at bulk-solvent model (Jiang & Brunger, 1994) and overall anisotropic Bfactor correction were applied.…”
Section: Re®nement Protocolsmentioning
confidence: 99%
“…et al, 1997; Pannu et al, 1998). Thus, even single isomorphous replacement (SIR) phases from one heavy-atom derivative can be useful.…”
Section: Introductionmentioning
confidence: 99%
“…Use of the partial free data concept (Lunin & Skovoroda, 1995) showed that the refinement was successful. As a consequence, ML refinement has been widely adopted by the crystallographic community (Pannu & Read, 1996;Bricogne & Irwin, 1996;Murshudov et al, 1997;Adams et al, 1997;Pannu et al, 1998). Today, the free, model-unbiased fraction of data typically consists of 5% of the diffraction data.…”
Section: Introductionmentioning
confidence: 99%